2018
DOI: 10.22270/jddt.v8i2.1563
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Colon Targeted Delivery of Tegaserod Maleate for Irritable Bowel Syndrome

Abstract: The colon is being extensively investigated as a drug delivery site. Colonic drug delivery is a relatively recent approach for the treatment of diseases like ulcerative colitis, Crohn's disease, and irritable bowel syndrome. To achieve successful colon targeted drug delivery, a drug needs to be protected from degradation, release and /or absorption in upper portion of GI tract and then ensure abrupt or controlled release in proximal colon. The purpose of this research is to develop and evaluate the polysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The coating on the tablets was created by combining galactosyl, xanthan gum, and chitosan polysaccharide in varying amounts. The in-vitro dissolution investigation found that when compared to galactose and chitosan, xanthan gum demonstrated more sustained drug release due to enzymatic breakdown in the presence of rat caecal material [ 56 ].…”
Section: Reviewmentioning
confidence: 99%
“…The coating on the tablets was created by combining galactosyl, xanthan gum, and chitosan polysaccharide in varying amounts. The in-vitro dissolution investigation found that when compared to galactose and chitosan, xanthan gum demonstrated more sustained drug release due to enzymatic breakdown in the presence of rat caecal material [ 56 ].…”
Section: Reviewmentioning
confidence: 99%